IMPROVING ORGANIZATIONAL AND ECONOMIC DEVELOPMENT OF THE FOOD INDUSTRY BY IMPLEMENTING THE EXPERIENCE OF DEVELOPED COUNTRIES (European Journal of Economics, Finance and Business Development, 2025)
It is known that the total population of the world is growing rapidly. In particular, according to the analyzes of the United Nations (UN), the world population in 2024 will be 8.2 billion. person, this indicator will reach 9.7 billion by 2050. it is expected to reach a person [1]. In addition, the problem of not being able to provide the population with food products in many countries due to factors such as the geopolitical problems that have occurred in the last 10-15 years and the impact of global climate changes on the economy, structural changes in economic processes, as well as the reduction of irrigated land and increasing drought being observed.